Effect of Ethical Accounting Practices on Quality Financial Reporting in Manufacturing Firms in Rwanda: Case of Sulfo Rwanda Industries - Kwihangana , Emmanuel; Tarus , Thomas (Journal of Finance and Accounting, 2024)
Manufacturing industries like Sulfo Rwanda is facing the issues of quality financial reports such as the users lack of getting full understanding about all company operations and activities, delay in reports, there is some manipulating of accounting figures. The main purpose of the study was be to examine the effect of ethical accounting practices on quality financial reports in manufacturing firms in Rwanda. To establish the effect of objectivity on quality financial reports in Sulfo Rwanda industries, to examine the effect of professional competence on quality financial reports in Sulfo Rwanda industries, to analyze the effect of integrity on quality financial reports in Sulfo Rwanda industries. The study was use descriptive research design. The study population was be composed only 43 employees of Sulfo Rwanda industries working in department fitting to provide concerning to the study objectives. This study was use purposive sampling techniques for selecting 43 employees working in Sulfo Rwanda industries as respondents. Descriptive statistics was use to analyze quantitatively, Mean, standard deviation and regression analysis was be taken into consideration to make the analysis. A statistical package for Social Sciences (SPSS) version 22.0 was use to analyze the data collected throughout a questionnaire. Regression results indicate the coefficient of objectivity was (β1=0.453, p=0.008, <0.05 level of significance) showed a statistically significant relationship between objectivity and quality financial reports in Sulfo Rwanda industries. The coefficient of professional competence was (β2=0.355, p=0.000, <0.05 level of significance) showed a statistically significant relationship between professional competence and quality financial reports in Sulfo Rwanda industries. The coefficient of integrity was (β3= 0.192, p=0.004, <0.05 level of significance) showed that integrity has positive and significant effect quality financial reports in Sulfo Rwanda industries. The coefficient of independence was (β4=0.605, p=0.002, <0.05 level of significance) showed a statistically significant relationship between independence and quality financial reports in Sulfo Rwanda industries. Sulfo Rwanda industries should invest in ongoing training and development programs for its financial professionals. This will ensure that the workforce possesses the necessary skills and knowledge to maintain high standards in financial reporting.